Administrative Skills in the 21st Century of School Administrators under Vocational Education, Chachoengsao Province - Kairdsawat, Parichat (Interdisciplinary Academic and Research Journal, 2023)
Nowadays, it is a society of change and a society of continuous learning, school administrators and executives of various departments cannot stop developing themselves but must learn continuously to prepare themselves. and their organizations to cope with changes over time and quickly. School administrators must have administrative skills, academic leadership, knowledge, and professionalism to be effective leaders and effective management for organizational development. Thus, the purpose of this research is (1) To study administrative skills in the 21st century of school administrators under vocational education in Chachoengsao Province. And (2) to compare the level of opinions towards management skills in the 21st century of school administrators under vocational education in Chachoengsao Province classified by gender, work experience, and teaching level. The population in this research consisted of 569 vocational educational institutes in Chachoengsao Province using a sample of 229 people. The research tool was the questionnaire on management skills in the 21st century. The statistics used in the research were frequency, mean, percentage, standard deviation, F-test, and t-test. The results showed that (1) management skills in the 21st century of school administrators under vocational education in Chachoengsao Province were generally at a high level. And (2) the results of a comparative analysis of opinions on the management skills in the 21st century of vocational education institute administrators in Chachoengsao Province, both overall and in terms found that; (a) classified by gender, the overall difference was statistically significant at the .05 level, while the individual differences were in terms of communication skills. (b) Classified by work experience in general, there is no difference, but in terms of creative skills. And (c) Classified by the teaching level as a whole and each aspect was not different.